Culinary Linguistics The Chef's Special - Gerhardt, Cornelia; Frobenius, Maximiliane; Ley, Susanne (John Benjamins Publishing Company, 2013)
Language and food are universal to humankind. Language accomplishes more than a pure exchange of information, and food caters for more than mere subsistence. Both represent crucial sites for socialization, identity construction, and the everyday fabrication and perception of the world as a meaningful, orderly place. This volume contains an introduction to the study of food and an extensive overview of the literature focusing on its role in interplay with language. It is the only publication fathoming the field of food and food-related studies from a linguistic perspective. The research articles assembled here encompass a number of linguistic fields, ranging from historical and ethnographic approaches to literary studies, the teaching of English as a foreign language, psycholinguistics, and the study of computer-mediated communication, making this volume compulsory reading for anyone interested in genres of food discourse and the linguistic connection between food and culture.